An Analysis of Teachers Questioning Strategy at the Computer Engineering Class of SMKN 7 Luwu Utara - Tsamratul'aeni Tsamratul'aeni (Universitas Cokroaminoto Palopo, 2021)
The objective of this research is to find out the teachers’ questioning strategy in teaching English at SMKN 7 Luwu Utara. The method that was applied in this research is a descriptive qualitative method. There were 2 English teachers as the sample of this research. Data collection of this research through interview and questionnaire. The result of data analysis showed that the teachers used questioning strategies by applying some types of question in each sessions of teaching. During the interview the researcher found that the first teacher only used a probing question and divergent question, while the second teacher only used a higher order question. So, from the whole between the first teacher and the second teacher after the researcher analyzed from the interview and questionnaire, the researcher found that the questioning strategies used by the teacher were probing questions, divergent questions and higher order questions. As for the strategy question that often appears or is often used by teachers, namely the probing question strategy.